Accounting for a Beggar's Life (Phenomenological Study in Pragaan Daya Sumenep Regency) - Ainorrofiqie; An-Nisa Zhafarina Qashri (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This research examines the paradigm of society in Daya Madura in relation to its tradition of begging. This study is based on the fact that begging is no longer just a temporary solution to their economic problems, but has become a permanent job to cope with the burden of life. Using a phenomenological approach, this study attempts to answer the main problem, namely the background of the beggar's life and the accounting motivations within it. In this study, the analysis is carried out to find out the financial management of beggars, and it can be done on the basis of the accounting equation, but in its application, not all the accounts included in the accounting equation are used in the financial management of the beggars' accounting. The accounting practice of beggars requires only approximate income and expenses. Also in this study, we can see that accounting not only focuses on calculation techniques and numbers, but also has value and importance.